Foxes in the snow [compact disc] - Isbell, Jason; Isbell, Jason (Southeastern Records, 2025)
Grammy Award-winning singer/songwriter Jason Isbell is one of the most respected and celebrated artists of his generation. The North Alabama native possesses an incredible penchant for identifying and articulating some of the deepest, yet simplest, human emotions, and turning them into beautiful poetry through song. Isbell sings of the everyday human condition with thoughtful, heartfelt, and sometimes brutal honesty. After releasing multiple albums and touring the world with his band, the 400 Unit, Isbell will begin 2025 with a change of pace. He will hit the road on his own, performing solo at historic music venues across Europe and the US. In conjunction with these much anticipated shows, Isbell will release a new album featuring only his voice and an acoustic guitar. These recordings further demonstrate his pure talent as a songwriter and musician.